Laboratory simulation of recent NAPL spills to investigate radon partition among NAPL vapours and soil air. (February 2017) - De Simone, Gabriele; Lucchetti, Carlo; Pompilj, Francesca; Galli, Gianfranco; Tuccimei, Paola
Abstract: Soil radon is employed to trace residual NAPL (Non-Aqueous Phase Liquid) contamination because it is very soluble in these substances and is strongly depleted over polluted volumes of the subsoil. The solubility of radon into NAPL vapors, generally poorly considered, is investigated here, either as growth of radon exhalation from a material contaminated with increasing volumes of kerosene, or as radon partition between liquid kerosene, water and total air, considered ad the sum of kerosene vapors plus air. Highlights: Laboratory simulation of recent NAPL spills was carried out Kerosene vapors enhance soil radon exhalation and transport The use of desiccants emphasizes radon preferential dissolution into NAPL vapors Radon partitioning among liquid kerosene, water and total air is investigated Radon partition coefficients between liquid and vaporized kerosene were estimated